PENGARUH SIMPLIFIKASI PROSEDUR PELAYANAN MASYARAKAT TERHADAP TINGKAT KEPUASAN MASYARAKAT PELAYANAN PERPANJANGAN SURAT IJIN MENGEMUDI DI SATPAS POLRESTABES KOTA MAKASSAR - Nuralamsyah Dwi Saputra; Rosnaini Daga; Hendra Gunawan (Jurnal Sains Manajemen Nitro, 2023)
The formulation of the problem in this research is Does Simplification of Customer Procedures affect Customer Satisfaction of Driver's License (SIM) at Traffic Police of Makassar City? Does the Efficiency of Customer Simplification Affect Customer Satisfaction of a Driver's License (SIM) at the Makassar City Police Traffic Unit? Does the Simplification Effectiveness Procedure affect Driver's License (SIM) Customer Satisfaction at the Makassar City Police Traffic Unit? Does the Cost Element Affect Customer Satisfaction of Driver's License (SIM) at Traffic Traffic Makassar City Police? Does Time Acceleration Affect Driver's License (SIM) Customer Satisfaction at Traffic Traffic Makassar City Police? Does Service Innovation affect Driver's License (SIM) Customer Satisfaction at Traffic Traffic Makassar City Police? This research was conducted at Polrestabes Makassar City. The sampling technique used Purposive Sampling to 90 responden consumer SIM administrators at Polrestabes Makassar City. The reason for determining the object of this research is because it is easily accessible by researchers so that it can facilitate the implementation of research. From the results of the study it can be concluded that the Procedure Factor has a positive and significant influence on the Satisfaction of STNK Management at the Wajo District Police. The procedural factor has a positive and insignificant effect on SIM applicant satisfaction at the Makassar City Police. The efficiency factor has a negative and insignificant effect on SIM applicant satisfaction Makassar City Police. The effectiveness factor has a positive and insignificant effect on SIM applicant satisfaction Makassar City Police. Cost Element Factors have a positive and not significant impact on SIM Applicant Satisfaction Makassar City Police. The time acceleration factor has a positive and insignificant effect on SIM applicant satisfaction at the Makassar City Police. 6. The innovation factor has a positive and significant influence on the satisfaction of SIM applicants at the Makassar City Polrestabes.